The structure–activity relationship and computational studies of 1,3-thiazole derivatives as cholinesterase inhibitors with anti-inflammatory activity - Modrić, Marina; Božičević, Marin; Odak, Ilijana; Talić, Stanislava; Barić, Danijela; Mlakić, Milena; Raspudić, Anamarija; Škorić, Irena (Comptes Rendus. Chimie)
In our previous research, some screened 1,3-thiazole fragments were found to be potent by inhibiting LPS-induced TNF$α $ and IL-8 release with IC50 values in the $μ $M range without cytotoxic activity. In the current study, 1,3-thiazole fragments were further investigated as potent cholinesterase inhibitors prompted by the previously documented anti-inflammatory effect of AChE inhibitors. Molecular docking enabled insight into stabilizing interactions between the selected thiazoles and the active site of AChE and BChE. According to these experimental results, the cholinesterase inhibitory and anti-inflammatory activity of 1,3-thiazoles were correlated and confirmed that the same compounds inhibited LPS-stimulated TNF$α $ cytokine production in PBMCs and enzymes cholinesterases.